Theory advancing practice: The Contingency Theory in the strategic management of crises, conflicts, and complex public relations issues - PANG, A. (Institutional Knowledge at Singapore Management University, 2024)
If the news headlines are to be believed in their entirety, the world seems to be traversing from one crisis to another. COVID-19 was the black swan no one predicted. Even before the world emerged from the worst parts of the pandemic, Russia’s unprovoked invasion of Ukraine triggered global security concerns. In addition to the ongoing tensions between the United States (US) and China, US and Russia, Mainland China and Taiwan, and at the point of writing, the crisis between Ukraine and Poland over grain imports, one gets the impression that the world is in a fiery cauldron of turmoil. No wonder the Year in a Word for 2022 was “polycrisis.” A term popularized by historian Adam Tooze (2022), it described how global crisis are interconnected, intertwined, with simultaneous occurrence of catastrophic events